Multicentre, multitime, multidimension, prospective follow-up cohort study on patients during the first wave of COVID-19 in China: a study protocol - Ming Zhang; Xuan Niu; Tonghui Liu; Chao Zheng; Huijie Yuan; Yanan Zhu; Huiping Liu; Shan Wu; Zhaoyao Luo; Jia Zhu; Danwei Hou; Tianhua Wei; et al. (BMJ Open)
Introduction During the first wave of the COVID-19 outbreak in China, the surge of COVID-19 cases was rapid and drastic. Emerging evidence suggests that beyond the acute phase, patients with COVID-19 may experience a wide range of postacute or long COVID sequelae. However, the mechanism and burden of COVID-19, especially long COVID, have not yet been comprehensively clarified. To fill this knowledge gap, this large prospective follow-up study aims to investigate the short-term and long-term effects of COVID-19, explore the underlying biological mechanism and identify predictive neuroimaging and haematological biomarkers associated with these effects.Methods and analysis This multicentre study will recruit patients infected during the first wave of COVID-19 in China and healthy controls (HCs) with no history of COVID-19 infection from nine participating hospitals. Confirmed patients with mild or moderate COVID-19 will complete the following programmes during the acute infection phase and at 3, 12 and 24 months after infection: (a) blood test at the local laboratory, (b) multimodal brain and spine MRI scan and (c) the neuropsychological scales and questionnaires. Similarly, the uninfected HCs will complete the same programmes as the infected group mentioned above at the time of inclusion. At the first time point, 501 participants (418 patients and 83 HCs) from nine recruiting hospitals have been observed. Ultimately, all of these results will be analysed to explore the short-term and long-term effects of COVID-19.Ethics and dissemination Ethics approval was granted by Ethics Committee of the First Affiliated Hospital of Xi'an Jiaotong University (XJTU1AF2023LSK-013). Findings will be presented at national and international conferences, as well as published in peer-reviewed scientific journals.Trial registration number NCT05745805.